The Roots of Trust - Mújdricza, Ferenc (European Journal of Mental Health, 2019)
The present article addresses the question of the ‘roots’ of trust: a debate between cognitive and non-cognitive trust theories, ongoing since the dawn of modern theorising on trust. On the one side, there is the assumption of conceiving trust as a learnt capacity, based on Erikson’s concept of basic trust. On the other side is the hypothesis of innate, built-in trust. After a critical overview of the cognitive and non-cognitive approaches, given that neither side was able to build up a decisive argument, the paper proceeds to some relevant discoveries of the life sciences that serve as proofs of the concept. Michael Polányi’s principles of marginal control and boundary conditions help avoiding the pitfall of any reductionist determinism. The analysis results in a rejection of the early learning concept of the cognitive approaches. Trusting is proven to be an a priori given human faculty inscribed in our neurobiological system, but neither biologically, nor in any other way, entirely determined. The possibility to trust is always present in the human: the trusting being.